Men and women, so different, so similar: observations from cross‐sex hormone treatment of transsexual subjects. (19th May 2013) - Gooren, L. J.; Giltay, E. J.
Summary Sexual differentiation in mammals is largely driven by the presence of androgen in males and their absence in females. The presence of androgens induces a number of irreversible changes in males: prenatally, the genital differentiation; during puberty, the development of secondary sex characteristics – the larger facial bones, hand, feet and height in males. A large number of metabolic variables are influenced by sex hormones and consequently show difference between men and women, and this helps to explain differences in pathologies, such as cardiovascular disease, bone fractures and auto immune disease. There is some recent evidence that some sex differences in brain functions are not mediated by sex hormones, but by‐products of genes located on the X and Y chromosomes. This communication reviews the results of administration of cross‐sex hormone treatment to transsexual persons transitioning to the other sex. Natal males are treated with anti‐androgens+oestrogens and natal females with testosterone. This provides a unique opportunity to study which metabolic functions are not irreversibly sex‐differentiated but are determined by the prevailing milieu of sex steroids. The insights gained with these studies should lead to a better appreciation of the role of sex steroids in cardiovascular disease and diabetes mellitus which presently do not receive due attention.